Differences in Motivation to Learn Arabic in Terms of Gender In the Islamic Religious Education Study Program - Syawaluddin Syawaluddin; Bambang Trisno; Lainah Lainah; Yogi Damai Syaputra; Halida Halida (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2023)
The Arabic language is a compulsory course for all students of IAIN Bukittinggi. This lesson requires high learning motivation to achieve excellent learning outcomes. This research focused on the influences of gender differences on Arabic language course learning motivation. This research determined the Arabic course learning motivation differences based on gender among students in the Islamic Education (PAI) study program at the IAIN Bukittinggi. The researchers applied a quantitative comparative approach. The population comprises students in the Islamic Education study program at the IAIN Bukittinggi who are in the third semester. The participants consisted of 199 students. The researchers applied total sampling. The instrument used in this study was the learning motivation scale. The researchers analyzed the data with a hypothetical mean formula, while the hypothesis test was with the Analysis of Variance, ANOVA. The results showed that the male Arabic learning motivation was high, with a mean score of 130.3, while the female Arabic learning motivation was 126.4. The hypothesis test found a significant value of 0.277 lower than 0.5. The results indicated a significant difference between male and female Arabic language learning motivations. However, when looking at the overall average scores, the motivation of male students to learn Arabic is higher than female students. Based on the results of this study, it suggested that counselors provide Guidance and Counseling services, primarily focusing on indicators of self-reliance in learning Arabic. It is expected that with guidance and counseling services, students can enhance their motivation to learn Arabic, particularly in terms of self-reliance in learning.